Model Aptitude Treatment Interaction untuk Meningkatkan Pemahaman Konsep Matematika di Sekolah Dasar - Rahma, Fadila; Kurniawan, Akil (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2025)
The Aptitude Treatment Interaction (ATI) learning model is a differentiated approach that aligns instructional strategies with students’ initial abilities to improve learning outcomes. This classroom action research aimed to examine the planning, implementation, and effectiveness of the ATI model in enhancing the mathematical conceptual understanding of third-grade students at UPT SDN 013 Kumantan. The study was conducted in two cycles, each consisting of two sessions. Data collection techniques included observation, documentation, and written tests. Data analysis employed both qualitative and quantitative methods. The findings show a progressive increase in students' conceptual understanding from the pre-cycle to cycle II. In the pre-cycle, only 36.36% of students met the minimum mastery criteria (MMC). After the first cycle, the mastery level improved slightly to 54.55%, and significantly increased to 81% in the second cycle. This improvement met the predetermined MMC benchmark, indicating that no further cycle was needed. The results demonstrate that the ATI model effectively addresses student diversity and helps tailor instructional methods to meet individual needs. The model not only improved students’ conceptual understanding of mathematics, particularly on angle measurement topics, but also fostered greater motivation and participation. It is recommended that teachers adopt and adapt the ATI model to various subjects to promote inclusive and responsive classroom instruction.